2020
DOI: 10.1111/1541-4337.12663
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamic acids on gut microbiota and health

Abstract: Hydroxycinnamic acids (HCAs) are a major class of phenolic acids with the characteristic phenylpropanoid C6‐C3 backbone. Its typically conjugated status with plant cell wall components and liberation by limited enzymes might be the reason for its neglect by researchers compared to flavonoid‐type polyphenols. The polyphenol–gut microbiota interactions and their impact on human health have captured the interest of researchers recently. In addition, there has been a significant progress over the past few years in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 138 publications
0
58
0
Order By: Relevance
“…However, to our knowledge, only in the study by Wang et al (2016) [ 20 ] the changes in gut microbiota induced by the ingestion of BG were associated with anthropometric parameters, meaning that the increase in the proliferation of Bacteroidetes, Bacteroides and Prevotella counts correlated with a positive shift in BMI and WC, along with a reduction in Firmicutes and Dorea counts [ 20 ]. On the other hand, regarding hydroxycinnamates, both in vivo and in vitro studies demonstrate the efficacy of these compounds in modulating the gut microbiota (reviewed in Leonard et al [ 57 ]). Among the studies in this review outstands that carried out in C57BL/6J female mice that showed an increment in the population of Akkermansia and a decrease in Firmicutes after a 15-day treatment with 1.8 mg/kg of body weight per day of pure caffeic acid [ 58 ], and that carried out in ICR mice that showed an increase in Bacteroidaceae and Lactobacillaceae and a decrease in Desulfovibrionaceae, Ruminococcaceae, Lachnospiraceae and Erysipelotrichaceae populations after daily consumption of 150 mg/kg by body weight of pure chlorogenic acid [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, only in the study by Wang et al (2016) [ 20 ] the changes in gut microbiota induced by the ingestion of BG were associated with anthropometric parameters, meaning that the increase in the proliferation of Bacteroidetes, Bacteroides and Prevotella counts correlated with a positive shift in BMI and WC, along with a reduction in Firmicutes and Dorea counts [ 20 ]. On the other hand, regarding hydroxycinnamates, both in vivo and in vitro studies demonstrate the efficacy of these compounds in modulating the gut microbiota (reviewed in Leonard et al [ 57 ]). Among the studies in this review outstands that carried out in C57BL/6J female mice that showed an increment in the population of Akkermansia and a decrease in Firmicutes after a 15-day treatment with 1.8 mg/kg of body weight per day of pure caffeic acid [ 58 ], and that carried out in ICR mice that showed an increase in Bacteroidaceae and Lactobacillaceae and a decrease in Desulfovibrionaceae, Ruminococcaceae, Lachnospiraceae and Erysipelotrichaceae populations after daily consumption of 150 mg/kg by body weight of pure chlorogenic acid [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, coffee supplementation might even be beneficial to the gut, as shown by the reduction in the bloom of Proteobacteria in the caffeinated coffee-treated groups. Since coffee is one of the most polyphenol-rich and caffeine-rich foods we consume ( Leonard et al, 2020 ), these results may also give us information about the extent to which polyphenols, particularly chlorogenic acid, and caffeine individually impact the composition of the microbiome. This is an important step in increasing our knowledge of dietary means to prevent or treat antibiotic-induced dysbiosis and its associated diseases, an increasing problem as antibiotic use continues to rise worldwide ( Klein et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids (PAs) are a group of nonflavonoid phenolic compounds that contain a single phenyl group substituted by a carboxylic group and one or more hydroxyl (OH) groups [ 25 ]. PAs are further divided according to the length of the chain that contains the carboxylic group into: hydroxybenzoic acids, hydroxycinnamic acids, and hydroxyphenyl acids.…”
Section: Caffeic Acid As a Phenolic Compoundmentioning
confidence: 99%